Determinants of Postnatal Care and Timing of the First Postnatal Care for Newborns in Ethiopia: Further Analysis of 2019 Ethiopian Demographic and Health Survey - Sewnet Adem Kebede; Adisu Birhanu Weldesenbet; Biruk Shalmeno Tusa (Frontiers Media S.A., 2022)
BackgroundNeonatal mortality remains a persisting public health challenge in Ethiopia. Most of the factors that lead to neonatal deaths could be prevented through postnatal checkups. However, in Ethiopia, the provision of postnatal care (PNC) continues to be low. This study aims to assess the socioeconomic and demographic factors associated with PNC visits and the timing of PNC among newborns in Ethiopia.MethodsUsing the Ethiopia Mini Demographic and Health Survey (EMDHS) 2019, a total weighted sample of 2,105 women aged 15-49 giving birth in the 2 years preceding the survey were included in the study. The generalized linear mixed models were separately fitted to identify factors associated with any PNC for newborns delivered at home and health facilities. Multinomial logistic regression was used to assess the timing of PNC with their associated factors.ResultsOverall, only 13% (95% CI: 11.2, 14.0) of the newborns received PNC in Ethiopia. Among newborns delivered at home, utilization of any PNC was determined by region, maternal educational status, and birth order. On the other hand, among newborns delivered in a health facility, region, number of antenatal care (ANC) visits, and religion were determinants of any PNC. Furthermore, utilization of the first PNC within 48 h after the delivery was determined by region and religion. On the other hand, utilization of the first PNC after 48 h after the delivery was determined by region number of ANC visits, maternal educational status, and religion.ConclusionThe finding of the current study revealed low coverage of PNC among newborns regardless of the place of delivery in Ethiopia. The study makes the following recommendation: increase community health education on PNC, encourage delivery at health facilities, and link community home birth with PNC. It will be more valuable if there is sharing good practice.